THE TRANSLATION SCENE IN INDEPENDENT LATVIA BETWEEN THE WARS (1918–1940) - Veisbergs, Andrejs (Vertimo studijos, 2017)
Latvia’s brief period of independence (1918/20–1940) saw book publishing on a massive scale. The range of source languages was growing, with English slightly ahead of German in the prewar years (German was the main intermediary language), followed by French and Russian. The literature translated was extremely varied in kind and quality: the choice of works to be translated was very much in the hands of translators and publishers. With the advent of cheap books, print runs grew longer and high-quality literature became accessible to a wider public. The share of translations among books fluctuated, although there were consistently more translated novels than domestically produced fiction. A large number of translators were also well-known writers in their native Latvian. Members of other professions frequently produced specialised translations and some individuals became professional translators from favourite source languages. Translator visibility grew with the status of the works translated. Translation criticism remained limited, mainly focusing on the quality of the Latvian, and lambasting pulp-literature translation in general.